2020
DOI: 10.1249/mss.0000000000002570
|View full text |Cite
|
Sign up to set email alerts
|

Sex Matters in the Association between Physical Activity and Fitness with Cognition

Abstract: Purpose: The benefits from physical activity (PA) and cardiorespiratory fitness (CRF) on normal age-related cognitive decline might be sex dependent. Our aim was to explore the relationship between different types of PA, CRF, and cognition and to identify the mediating effects of CRF in the association between PA and cognition in women and men. Methods: We recruited 115 healthy adults 50-70 yr of age. We obtained demographic, cognitive, and PA status data based on the Projecte Moviment protocol. We calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…However, we found that sex moderated the effects of the intervention on brain volumes on AE (total WM, parietal, temporal, and dorsolateral prefrontal cortex) and COMB groups (ventricles, temporal and dorsolateral prefrontal cortex) suggesting that men may benefit more than women. These results are consistent with our previously published results ( Castells-Sánchez et al, 2019 , 2020 , 2021 ) and the larger adaptations that men might experience after exercise, as suggested in previous research ( Al-Mallah et al, 2016 ). Moreover, these findings add support to the literature highlighting biological sex as a relevant moderator of the relationship between exercise and brain health ( Barha and Liu-Ambrose, 2018 ; Barha et al, 2019 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, we found that sex moderated the effects of the intervention on brain volumes on AE (total WM, parietal, temporal, and dorsolateral prefrontal cortex) and COMB groups (ventricles, temporal and dorsolateral prefrontal cortex) suggesting that men may benefit more than women. These results are consistent with our previously published results ( Castells-Sánchez et al, 2019 , 2020 , 2021 ) and the larger adaptations that men might experience after exercise, as suggested in previous research ( Al-Mallah et al, 2016 ). Moreover, these findings add support to the literature highlighting biological sex as a relevant moderator of the relationship between exercise and brain health ( Barha and Liu-Ambrose, 2018 ; Barha et al, 2019 ).…”
Section: Discussionsupporting
confidence: 94%
“…Cognitive changes in Executive Function and Attention-Speed in the AE group and in Attention-Speed in the COMB group were previously published ( Roig-Coll et al, 2020 ) and led us to address other micro and macroscopic correlates that might be involved in these interventions. We previously found that regular exercise was related to the inflammatory profile, brain volume and cognition in a cross-sectional sample ( Castells-Sánchez et al, 2020 , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is a cross-sectional study based on Projecte Moviment (Castells-Sánchez et al, 2019) and is drawn from our previously published results (Castells-Sánchez et al, 2020). The study was carried out by the University of Barcelona in collaboration with Institut Universitari d'Investigació en Atenció Primària Jordi Gol and Hospital Germans Trias i Pujol.…”
Section: Methodsmentioning
confidence: 99%
“…Identifying these pathways by which the benefits of exercise are realized is a challenge not only due to the multilevel mechanisms but also because of the role of factors that may moderate the association such as sex (Barha et al, 2019). Previous evidence suggests that both women and men might positively benefit cognition from exercise, although the CRFcognition relationship was only significant in men (Castells-Sánchez et al, 2020). Moreover, there are sex differences in the mediators of this relationship described in the ongoing research.…”
Section: Introductionmentioning
confidence: 93%
“…It also underlines the benefits of a low-cost high-impact lifestyle intervention on healthy aging, which might lead to long-term molecular, structural, and functional long-term neuroprotective benefits (Stillman et al 2016 ). In our previous cross-sectional studies, we reported a positive relationship between physical exercise and an inflammatory profile, brain volume, and cognition (Castells-Sánchez et al 2020 , 2021 ); however, we could not replicate the molecular and brain volume imaging findings after implementing the RCT (Castells-Sánchez et al 2022 ). Similarly, although previous cross-sectional studies (Gow et al 2012 ; Johnson et al 2012 ; Liu et al 2012 ) showed that higher PA levels are related to increased global FA and local FA levels in the corpus callosum, superior longitudinal fasciculus and arcuate fasciculus, several RCT failed to find significant changes on WM microstructure (Clarck et al 2019 ; Sexton et al 2020 ; Voss et al 2013 ).…”
Section: Discussionmentioning
confidence: 67%